Analisa Usability Aplikasi Feldiriz Costume Menggunakan Metode End User Computing Satisfaction dan PIECES - Fatha Alsidqi Husaini; Agung Triayudi; Ben Rahman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Feldiriz Costume is an application to make buying and selling transactions online, where users can choose a variety of available products and can buy these products in the application online. In an application, of course, it requires a beautiful and comfortable appearance when interacting with users. To maintain a positive image of the application, a usability evaluation of an application display and user comfort in using the application is made. the evaluation aims to measure the level of satisfaction for users of the Feldiriz Costume application. there are two methods used, namely End User Computing Satisfaction and PIECES. both methods are used to find the level of user satisfaction. the End User Computing Satisfaction got a score of 4,498 with a very satisfied level of user satisfaction. and the PIECES method got a score of 4.38 with a very satisfied level of user satisfaction. besides that, it also uses the PageSpeed Insgihts tool to assess the performance of the various pages available in the Feldiriz Costume application. In the assessment, PageSpeed Insights got an average performance score of 97, this shows that the Feldiriz Costume application is in the good category.